(3BOGH GdYGde hGdeJYdes - (3Ydj Hf YHO Gddg Hf CMeO GdMSfj GdTGaYj, fhQ GdOjf CHh GdMSf,J (B911 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdgGOi Edi WQjb GdUhGH hHYO agPg cQGQjS eSJMHI ef cJGH LhGgQ GdYbOjf ai aVd GdTQajf TQa GdYde GdLdi hGdfSH GdfHhi s
(3BNQgG (B:s
(3Yf GHf YHGS QVi Gddg Yfg Gf fHi Gddg Udi Gddg Ydjg hSde bGd Cf GdgOi GdUGdM hGdSeJ GdUGdM hGdGbJUGO LRA ef NeSI hYTQjf LRA ef GdfHhI s
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai dgW (B1/ 614s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B307 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B129s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdSjGSI hGdGLJeGYs